High-pressure alkaline water electrolyser of coaxial configuration. Issue 5 (December 2020) - Kuleshov, V N; Kurochkin, S V; Kuleshov, N V; Udris, E Ya
Abstract: At present, hydrogen is increasingly being used in various industries. Moreover, among all technologies for producing hydrogen, the proportion of electrolytic hydrogen is constantly increasing. The most widely used technology is industrial water alkaline electrolysers of various capacities. In parallel, the direction associated with the development of high-pressure water alkaline electrolysers begins to develop. This paper considers the issue of creating and testing a high-pressure water alkaline electrolyser of coaxial configuration. Possible problems are considered during the operation of its components under high pressures, and ways to solve these problems. The proposed type of coaxial configuration and the changes made to the composition of the diaphragm material made it possible to reach a pressure of 100 bar.